Trading Policy Analysis of Cocoa in Indonesia - Duron, Marion Justin Jerico; Manalo, Ma. Patricia Isabelle; Reyes, Angelin Marian; ROSETE, Marie Antoinette L. (IJOSMAS, 2022)
Until 2010, the Indonesian cocoa exports had been dominated by cocoa beans, which led the government to stimulate the processing industry by implementing cocoa export tax policy. This study will investigate the impact of the tax tariff policy on the supply and demand of cocoa beans in Indonesia. The imposed ad valorem tariff of Indonesia cocoa beans will be investigated in order to know whether the domestic market is ready or not to absorb the quantity supply of cocoa beans, when the export demand quantity declines. This study aims to determine the impact of cocoa export trading policy on the competitiveness of cocoa beans as well as the integration of cocoa prices. Moreover, this research will further discuss if the export tax policy has no impact on the integration of domestic and international cocoa markets.